Examining the effect of sustainable practices on organisational performance – the moderated-mediation roles of top management commitment and procurement capability - Owusua Gyan, Doreen (KNUST, 2024)
A thesis submitted to the department of department of supply chain and information systems, institute of distance learning, in partial fulfilment of the requirements for award of degree of master of science (logistics and supply chain management)